Chemistry of dope for lubrication oils - Баранський, К. І.; Усаченко, С. М. (Proceedings of National Aviation University, 1998)
Given are theoretical foundations of highly efficient dopes for motor oils. Created on this basis competing motor oils for speedy highly-boosted transport engines and their series production is organized. Proposed are constructive and systematic methods of analysis of these dopes and their operation characteristics. Considered are theoretical foundations of synthesis methods of metallorganic dopes high efficiency of which is substained theoretically and practically